2016
DOI: 10.3762/bjnano.7.111
|View full text |Cite
|
Sign up to set email alerts
|

Influence of synthesis conditions on microstructure and phase transformations of annealed Sr2FeMoO6−x nanopowders formed by the citrate–gel method

Abstract: SummaryThe sequence of phase transformations during Sr2FeMoO6−x crystallization by the citrate–gel method was studied for powders synthesized with initial reagent solutions with pH values of 4, 6 and 9. Scanning electron microscopy revealed that the as-produced and annealed powders had the largest Sr2FeMoO6−x agglomerates with diameters in the range of 0.7–1.2 µm. The average grain size of the powders in the dispersion grows from 250 to 550 nm with increasing pH value. The X-ray diffraction analysis of the pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…By adding ethylenediamine (EDA) into two parts of this solution, their pH values were adjusted to 4 and 9, respectively. In previous works, we showed that the synthesis of Sr 2 FeMoO 6−δ powders obtained at the solution with a pH of 4 allowed obtaining films with maximum superstructural ordering, but the raising of pH decreased the degree of order superstructure . Finally, the obtained solutions were continuously stirred at 353 K until the light green gels were formed.…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…By adding ethylenediamine (EDA) into two parts of this solution, their pH values were adjusted to 4 and 9, respectively. In previous works, we showed that the synthesis of Sr 2 FeMoO 6−δ powders obtained at the solution with a pH of 4 allowed obtaining films with maximum superstructural ordering, but the raising of pH decreased the degree of order superstructure . Finally, the obtained solutions were continuously stirred at 353 K until the light green gels were formed.…”
Section: Methodsmentioning
confidence: 98%
“…The compound of Sr 2 FeMoO 6−δ system was prepared by the sol–gel method, using Sr(NO 3 ) 2 , Fe(NO 3 ) 3 ·9H 2 O (NH 4 ) 6 Mo 7 O 24 , and C 6 H 8 O 7 ·H 2 O as starting materials . At first, the aqueous solutions of Sr(NO 3 ) 2 (0.4 mol dm −3 ) and Fe(NO 3 ) 3 (2 mol dm −3 ) were mixed in a molar ratio of 2(Sr):(Fe), and then C 6 H 8 O 7 ·H 2 O was added to the solution in a molar ratio of 6.5(C 6 H 8 O 7 ·H 2 O):(Fe).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations